The complete mitochondrial genome of the kelp fly Fucellia costalis (Diptera: Anthomyiidae) from Pacific Grove, California. Issue 1 (2nd January 2019) - ; Agudelo, Ivan D.; Almanza, Karina; Guadalupe Altamirano Manriquez, Maria; Andrade, Paulina; Anguiano, Eduardo; Ayala, Sandra; Barrios, Dominic; Batistiana, Lyric; Battar, Kruthi; Noemi Benavides, Daisy; Chavez, Rafaela; et al.
Abstract: Genomic analysis of the kelp fly Fucellia costalis (Family Anthomyiidae) from Asilomar beach, Pacific Grove, California, resulted in the assembly of its complete mitogenome. The mitogenome is 16, 175 bp in length, A + T biased (78.1%), contains 37 genes, a large 1356 bp control region, and has a high-level of gene synteny to other Muscoidea. Phylogenetic analysis of F. costalis fully resolves it in a clade with two members of the Anthomyiidae, Delia platura (8.2% pairwise genetic distance) and D. antiqua (9.2% distance), in a sister position to Scathophaga stercoraria (7.8% distance) from the Scathophagidae. The phylogenetic position and genetic distances of F. costalis support the continued recognition of the subfamily Fucellinae. This identification and data extends the distributional range of F. costalis northward from California to Vancouver Island, Canada.